Corporate bankruptcy: the case of Kodak - McDonald, Michael (Henry Stewart Talks, 2015)
Corporate bankruptcy, Seniority in bankruptcy, Chapter 7 bankruptcy, Chapter 11 bankruptcy, Kodak: overview, Kodak’s chapter 11 bankruptcy process